2021
DOI: 10.3390/cancers13092049
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing with Liquid Biopsies from Treatment-Naïve Non-Small Cell Lung Carcinoma Patients

Abstract: Recently, the liquid biopsy (LB), a non-invasive and easy to repeat approach, has started to compete with the tissue biopsy (TB) for detection of targets for administration of therapeutic strategies for patients with advanced stages of lung cancer at tumor progression. A LB at diagnosis of late stage non-small cell lung carcinoma (NSCLC) is also being performed. It may be asked if a LB can be complementary (according to the clinical presentation or systematics) or even an alternative to a TB for treatment-naïv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 181 publications
0
19
0
Order By: Relevance
“…In this regard, many targeted sequencing methods, allowing for results in a short amount of time from cytological or blood specimens, have been used in many hospitals [64][65][66]. More recently, NGS methods have developed from these specimens, notably for EGFR status evaluation at baseline [67]. NGS approaches are of strong interest in order to detect different genomic alterations associated in genes other than EGFR, which may explain, at least partially, some primary resistance of TKIs targeting EGFR mutations [68].…”
Section: Biomarkers Assessed At Diagnosis With Cytological Samples And/or Liquid Biopsies Obtained From Advanced Non-squamous Non-small-cmentioning
confidence: 99%
See 4 more Smart Citations
“…In this regard, many targeted sequencing methods, allowing for results in a short amount of time from cytological or blood specimens, have been used in many hospitals [64][65][66]. More recently, NGS methods have developed from these specimens, notably for EGFR status evaluation at baseline [67]. NGS approaches are of strong interest in order to detect different genomic alterations associated in genes other than EGFR, which may explain, at least partially, some primary resistance of TKIs targeting EGFR mutations [68].…”
Section: Biomarkers Assessed At Diagnosis With Cytological Samples And/or Liquid Biopsies Obtained From Advanced Non-squamous Non-small-cmentioning
confidence: 99%
“…Moreover, it is crucial to detect an ALK fusion if a patient needs to be treated via immunotherapy due to an association of nonefficacy and of treatment toxicity of the immune checkpoint inhibitors (ICIs) in cases of ALK-positive tumors [73]. ALK status at baseline can be assessed not only in tissue biopsy but also in cytological specimens and in blood samples, notably on circulating free nucleic acids [47,67,74]. However, different studies demonstrated that the evaluation of ALK status can be made in circulating tumor cells at baseline.…”
Section: Alkmentioning
confidence: 99%
See 3 more Smart Citations